RP-HPLC method for simultaneous determination of atenolol and indapamide in pharmaceutical dosage forms, human blood and milk - Parusu, Thulasamma; Ponneri, Venkateswarlu (European Journal of Chemistry, 2012)
A simple, sensitive and precise high performance liquid chromatographic method for the analysis of atenolol and indapamide with UV detection at 231 nm, has been developed, validated and used for the determination of these compounds in pharmaceutical dosage forms, in human blood and in human milk. The compounds were well separated on a Hypersil BDS C18 reversed-phase column with mobile phase consisting of, pH = 3.5, 0.01 M potassium dihydrogen orthophosphate buffer-acetonitrile (60:40; v:v) at a flow rate of 1.0 mL/min. The method showed good linearity in the range of 5-30 µg/mL for atenolol and 0.25-1.50 µg/mL for indapamide. Both the drugs were eluted within 5 minutes and give sharp peak with high theoretical plate count and low tailing factor. The reaction time for atenolol and indapamide was found to be 2.29 and 3.83 min, respectively. The validation was carried according to International Conference on Harmonisation (ICH) guidelines. In linearity curve correlation coefficients for atenolol and indapamide were found to be 0.9995 and 0.9991, respectively. The percent recovery was 99.81-100.02 for atenolol and indapamide indicating accuracy and reliability of method. So the method can be used for estimation of these drugs in tablet dosage form, human blood and milk.